2001
DOI: 10.1063/1.1416478
|View full text |Cite
|
Sign up to set email alerts
|

Surface-modified CuO layer in size-stabilized single-phase Cu2O nanoparticles

Abstract: Activated reactive evaporation has been used to grow copper oxide nanoparticles in the size range of 8–100 nm. X-ray diffraction spectra clearly show the presence of a single Cu2O phase. Detailed x-ray photoelectron spectroscopy studies show an increase in the ionicity of the Cu2O system with decreasing particle size. Depth profiling and finger printing of x-ray photoelectron spectra reveal that the Cu2O nanoparticles are capped with a CuO surface layer of thickness ≈1.6 nm. This study strongly suggests that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 16 publications
12
78
0
1
Order By: Relevance
“…It shows clearly that at the surface, the Cu 2p 3/2 signal can be simulated as a summation of two peaks located at 932.2 eV and 933.5 eV respectively by using the Gaussian fit (not shown here), while that of the as-sputtered surface (the top 5 nm layer was sputtered off) only consists of the former component. [27] Due to the existence of Cu vacancy, the intrinsic Cu 2 O is conclusively p-type conductive, which has been supported by many theoretical and experimental research results. [28,29] However, some groups claimed that they obtained n-type Cu 2 O (especially those grown by using the electrodeposition method), and some explanations were put forward.…”
Section: Resultsmentioning
confidence: 58%
“…It shows clearly that at the surface, the Cu 2p 3/2 signal can be simulated as a summation of two peaks located at 932.2 eV and 933.5 eV respectively by using the Gaussian fit (not shown here), while that of the as-sputtered surface (the top 5 nm layer was sputtered off) only consists of the former component. [27] Due to the existence of Cu vacancy, the intrinsic Cu 2 O is conclusively p-type conductive, which has been supported by many theoretical and experimental research results. [28,29] However, some groups claimed that they obtained n-type Cu 2 O (especially those grown by using the electrodeposition method), and some explanations were put forward.…”
Section: Resultsmentioning
confidence: 58%
“…The grain size and the electric conductivity of the SrTiO 3 nanosolid increase with the annealing temperature [54]. Size-enhanced gas sensitivity of SnO 2 nanoparticles [52] and size-enhanced ionicity of Cu 2 O nanoparticles have also been observed [55]. Introducing ferroelectric materials of different sizes into a photonic crystal could modulate its refractive index and hence the photonic band gap, E G , which is sensitive not only to the external stimuli such as temperature or electric field, but also to the particle sizes.…”
Section: Overviewmentioning
confidence: 80%
“…Chen et al 18 have reported the synthesis of CuO shuttle-like nanocrystals via the hydrothermal decomposition route using the pre-obtained Cu(OH) 2 as the copper source in the absence of any surfactants. Synthesis of CuO nanorods and nanoribbons at the moderate temperature (77-82 ºC) in water-ethanol solutions were also reported by Chang et al 19 Balamurugan et al 20 reported the synthesis of nanosized CuO by the electrodeposition of Cu(II) ions followed by the gas-solid reaction. Kim and co-workers synthesized porous CuO nanowires by deposition of Cu on the porous single-walled carbon nanotube substrate followed by a thermal oxidation process.…”
Section: Introductionmentioning
confidence: 85%
“…Despite considerable efforts devoted to the preparation of the nanosized CuO, [15][16][17][18][19][20][21][22][23][24][25] there is a lack of information about ultrasonic-assisted (US) preparation methods especially US thermal decomposition and US liquid hydrolysis methods.…”
Section: Introductionmentioning
confidence: 99%